Comparison of Classical Test Theory and Item Response Theory in Individual Change Assessment. (November 2016) - Jabrayilov, Ruslan; Emons, Wilco H. M.; Sijtsma, Klaas
Clinical psychologists are advised to assess clinical and statistical significance when assessing change in individual patients. Individual change assessment can be conducted using either the methodologies of classical test theory (CTT) or item response theory (IRT). Researchers have been optimistic about the possible advantages of using IRT rather than CTT in change assessment. However, little empirical evidence is available to support the alleged superiority of IRT in the context of individual change assessment. In this study, the authors compared the CTT and IRT methods with respect to their Type I error and detection rates. Preliminary results revealed that IRT is indeed superior to CTT in individual change detection, provided that the tests consist of at least 20 items. For shorter tests, however, CTT is generally better at correctly detecting change in individuals. The results and their implications are discussed.